New pharmacovigilance course at the International Islamic University Malaysia-IIUM - Al-lela, Omer Qutaiba; Elkalmi, Ramadan Mohamed Mahmod; Jamshed, Shazia Qasim (American Association of Colleges of Pharmacy (AACP), 2013)
To the Editor. The Malaysian Adverse Drug Reactions Advisory Committee (MADRAC) was established under the Drug Control Authority (DCA) to perform the function of pharmacovigilance for drugs registered for use in Malaysia. It became a member of the World Health Organization (WHO) Program for International Drug Monitoring in 1990.1 Although MADRAC has invited healthcare professionals (physicians, pharmacists, dentists, etc) to submit adverse drug reaction (ADR) reports, the number of ADR reports submitted by healthcare professionals is considered low according to WHO recommendations for the optimal National Pharmacovigilance Centre.2 The most important reason for underreporting of ADR by healthcare professional is a lack of information3. .....